1997
DOI: 10.1083/jcb.138.2.395
|View full text |Cite
|
Sign up to set email alerts
|

KLP38B: A Mitotic Kinesin-related Protein That Binds PP1

Abstract: We have identified a new member of the kinesin superfamily in Drosophila, KLP38B (kinesin-like protein at 38B). KLP38B was isolated through its two-hybrid interaction with the catalytic subunit of type 1 serine/threonine phosphoprotein phosphatase (PP1). We demonstrate that recombinant KLP38B and PP1 associate in vitro. This is the first demonstration of direct binding of a kinesin-related protein to a regulatory enzyme.Though most closely related to the Unc-104 subfamily of kinesin-related proteins, KLP38B is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 88 publications
0
41
0
Order By: Relevance
“…KIF14 could share this function: PSORT II (http://psort.ims.utokyo.ac.jp/form2.html) predicts 78.3% probability of nuclear localization for KIF14 (despite the absence of a nuclear localization signal). Post-translational regulation of KLP38B activity is suggested by its in vitro association with protein phosphatase type 1 (PP1) (Alphey et al, 1997), while nebbish expression is regulated by the pRb/E2F system (Dimova et al, 2003). The KIF14 promoter contains E2F consensus binding sequences conserved between mouse and human (as determined by ConSite analysis, http:// mordor.cgb.ki.se/cgi-bin/CONSITE/consite), suggesting that similar regulation might function in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…KIF14 could share this function: PSORT II (http://psort.ims.utokyo.ac.jp/form2.html) predicts 78.3% probability of nuclear localization for KIF14 (despite the absence of a nuclear localization signal). Post-translational regulation of KLP38B activity is suggested by its in vitro association with protein phosphatase type 1 (PP1) (Alphey et al, 1997), while nebbish expression is regulated by the pRb/E2F system (Dimova et al, 2003). The KIF14 promoter contains E2F consensus binding sequences conserved between mouse and human (as determined by ConSite analysis, http:// mordor.cgb.ki.se/cgi-bin/CONSITE/consite), suggesting that similar regulation might function in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although chromosome arms can bind MTs in these spindles (Fuge, 1990;LaFountain et al, 2001), they do not display the extensive oscillations observed in vertebrate mitotic cells (D. Zhang, personal communication), presumably owing to the lack of a polar ejection force (LaFountain et al, 2001). Likewise, extensive metaphase chromosome oscillations do not occur in early Drosophila embryonic and Xenopus egg extract spindles (Maddox et al, 2002;BrustMasher and Scholey, 2002;Maddox et al, 2003), even though chromokinesins are present and play an important role in aligning chromosomes at the metaphase plate (Alphey et al, 1997;Vernos et al, 1995;Antonio et al, 2000;Funabiki and Murray, 2000). The extremely fast flux rates in these spindles probably produce a sufficiently high tension at kinetochores that the switch to the depolymerization state is prevented (Maddox et al, 2003) (Table 1).…”
Section: Looking Back To See Forwardmentioning
confidence: 99%
“…4 This finding is consistent with the known functions of the Drosophila homolog of KIF14, Klp38B, which binds chromatin, acts as a microtubule-dependent molecular motor (like all kinesins) and is involved in formation of the mitotic spindle. [5][6][7][8] In a microarray study, KIF14 expression was found to be cell cycle regulated with peak expression in S phase 9 ; the KIF14 promoter is bound by E2F4 and p130. 10 In summary, these data suggest that KIF14 plays an important role in mitosis.…”
mentioning
confidence: 99%